Development of an emulation method for the performance evaluation of radiant floor heating systems. (September 2014) - Rhee, KN; Yeo, MS; Kim, KW
Since radiant floor heating systems utilise part of the building as a system for controlling the indoor environment, the integrated analysis considering the interaction between the building and the system needs to be conducted for the performance evaluation. Integrated simulation can be applied for this purpose; however, it is somewhat difficult to evaluate the impact of the system hardware such as hydronic circuits and heat sources due to the lack of modeling information. Although the experimental methods can guarantee the most reliable results, they have a limitation on the repetitive comparison due to the restriction of time, space and cost. For this reason, this study presents an emulation method that can mitigate the disadvantage of the simulation as well as experimental methods, especially for the performance evaluation of radiant floor heating systems. To achieve this, the factors to be considered in radiant floor heating systems were examined by reviewing the previous studies on the emulation. This study suggested an emulation method that can physically represent pressure loss in the hydronic circuits and heat output from the floor structure, which are distinguishing features of radiant floor heating systems. With the developed emulation method, this study showed that the control performance and energy consumption of a radiant floor heating system can be investigated. Practical application: This study presents an emulation method to evaluate the energy consumption and control performance of radiant floor heating systems. The proposed emulation method will be able to supplement a pure simulation and to contribute to the development of an evaluation method considering the impact of system hardware on the overall performance of radiant floor heating systems. Therefore, it is expected that the results will be helpful to researchers for indoor environment, heating, ventilating and air conditioning engineers, system manufacturers and those who want to analyse the energy performance of radiant floor heating systems.